The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.jchf.2015.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Microvascular Inflammatory Endothelial Activation in Heart Failure With Preserved Ejection Fraction

Abstract: HFpEF is associated with coronary microvascular endothelial activation and oxidative stress. These lead to a reduction of NO-dependent signalling from endothelial cells to cardiomyocytes, which can contribute to the high cardiomyocyte stiffness and hypertrophy observed in HFpEF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
391
4
15

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 439 publications
(431 citation statements)
references
References 30 publications
21
391
4
15
Order By: Relevance
“…Previous data showed that diastolic dysfunction can be determined in the HFpEF animal model ZDF rat 23, 24. In accord with the literature we observed a significant increase in LV stiffness and prolonged relaxation time by pressure–volume analysis in our model.…”
Section: Discussionsupporting
confidence: 92%
“…Previous data showed that diastolic dysfunction can be determined in the HFpEF animal model ZDF rat 23, 24. In accord with the literature we observed a significant increase in LV stiffness and prolonged relaxation time by pressure–volume analysis in our model.…”
Section: Discussionsupporting
confidence: 92%
“…The subsequent inflammation could lead to frailty and could also negatively effect myocardial function ‘from a distance’ via the negative inotropic effects of the circulating cytokines (Mann, 2015). Interestingly, chronic inflammation and associated vascular dysfunction have also recently been linked to HFpEF (Paulus & Tschope, 2013; Glezeva et al ., 2015; Franssen et al ., 2016), the most common form of HF in the older adults (Upadhya et al ., 2015). Systemic inflammation can also accelerate skeletal muscle apoptosis and promote sarcopenia (Muscaritoli et al ., 2010).…”
Section: How Aging Frailty and Hf Interact To Induce Inflammationmentioning
confidence: 99%
“…Moreover, expression of both vascular cell adhesion molecule (VCAM) and E-selectin by endothelial cells favors migration of monocytes into the subendothelium, resulting in increased levels of TGF-␤ release and myocardial deposition of collagen (185,269). Recently, Franssen et al (71) provided comprehensive evidence for microvascular endothelial activation, high oxidative stress, endothelial nitric oxide synthase (eNOS) uncoupling, and low NO levels in the LV myocardium of HFpEF patients. These findings were reproduced in obese ZSF1 rats, which develop HFpEF at 20 wk of age, in contrast to lean ZSF1 rats (hypertensive controls), which maintain normal LV function after a similar time period.…”
Section: Altered Signaling Pathways In Hfpef As Potential Targets Formentioning
confidence: 99%